Project management metrics, KPIs, and dashboards : a guide to measuring and monitoring project performance - Kerzner, Harold (John Wiley & Sons, Inc., 2013)
The new edition of Harold Kerzner's bestselling book on measuring project management performance With today's complex projects, increased stakeholder involvement, and advances in computer technology, metrics and key performance indicators (KPIs) have become increasingly integral to informed decision-making and effective project management. Project Management Metrics, KPIs, and Dashboards, Second Edition helps functional managers gain a thorough grasp of what metrics and KPIs are and how to use them, as well as an understanding of different dashboard types, design issue.
Keywords: Project management.; Project management -- Quality control.; Performance standards.; Work measurement.; elektronické knihy; electronic books